Speed breeding in growth chambers and glasshouses for crop breeding and model plant research. Issue 12 (December 2018) - Ghosh, Sreya; Watson, Amy; Gonzalez-Navarro, Oscar; Ramirez-Gonzalez, Ricardo; Yanes, Luis; Mendoza-Suárez, Marcela; Simmonds, James; Wells, Rachel; Rayner, Tracey; Green, Phon; Hafeez, Amber; Hayta, Sadiye; et al.
Abstract 'Speed breeding' (SB) shortens the breeding cycle and accelerates crop research through rapid generation advancement. SB can be carried out in numerous ways, one of which involves extending the duration of plants' daily exposure to light, combined with early seed harvest, to cycle quickly from seed to seed, thereby reducing the generation times for some long-day (LD) or day-neutral crops. In this protocol, we present glasshouse and growth chamber–based SB approaches with supporting data from experimentation with several crops. We describe the conditions that promote the rapid growth of bread wheat, durum wheat, barley, oat, variousBrassica species, chickpea, pea, grass pea, quinoa andBrachypodium distachyon . Points of flexibility within the protocols are highlighted, including how plant density can be increased to efficiently scale up plant numbers for single-seed descent (SSD). In addition, instructions are provided on how to perform SB on a small scale in a benchtop growth cabinet, enabling optimization of parameters at a low cost. This protocol describes procedures for speed-breeding approaches using growth cabinets and LED-supplemented glasshouses. The approaches can be used to accelerate crop research and are compatible with a wide variety of crops.